2002
DOI: 10.1128/jcm.40.12.4659-4665.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tn 1546 in Vancomycin-Resistant Enterococcus faecium Isolated from Canine Urinary Tract Infections: Evidence of Gene Exchange between Human and Animal Enterococci

Abstract: Thirty-five enterococcal isolates were recovered from dogs diagnosed with urinary tract infections at the Michigan State University Veterinary Teaching Hospital over a 2-year period (1996 to 1998). Isolated species included Enterococcus faecium (n ‫؍‬ 13), Enterococcus faecalis (n ‫؍‬ 7), Enterococcus gallinarum (n ‫؍‬ 11), and Enterococcus casseliflavus (n ‫؍‬ 4). Antimicrobial susceptibility testing revealed several different resistance phenotypes, with the majority of the enterococcal isolates exhibiting re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 43 publications
4
66
2
3
Order By: Relevance
“…The enterococcal isolates carrying IS1542 have been reported in Europe (22). To our knowledge, no reports have been published from North America in regard to circulation of IS1542 in enterococcal populations (17). We were also able to detect IS1542 in the majority of our isolates (96%) originating from patients as well as surface water and hospital and municipal sewage, suggesting widespread dissemination of IS1542 among E. fae- (6), we also found that IS1542 and IS1216V elements were positioned at the left and right ends of transposons, respectively.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The enterococcal isolates carrying IS1542 have been reported in Europe (22). To our knowledge, no reports have been published from North America in regard to circulation of IS1542 in enterococcal populations (17). We were also able to detect IS1542 in the majority of our isolates (96%) originating from patients as well as surface water and hospital and municipal sewage, suggesting widespread dissemination of IS1542 among E. fae- (6), we also found that IS1542 and IS1216V elements were positioned at the left and right ends of transposons, respectively.…”
Section: Discussionsupporting
confidence: 51%
“…In this study, we found that 72% of our isolates obtained from all sources carried IS1216V. The presence of IS1216V has also been reported in majority of isolates obtained from Europe and North America (9,17), suggesting a global distribution of this IS. Furthermore, this IS has been reported in other species, such as Staphylococcus aureus (14).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Uncontrolled consumption of broadspectrum beta-lactams as well as long-term hospitalization influenced the spread of multidrugresistant bacteria; the treatment of such infections is difficult and may leads to mortality (3,5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus species show poor pathogenicity due to lack of powerful toxins and remarkable virulence factors, but since they are intrinsically insensitive to penicillins, aminoglycosides, and glycopeptides, and show high competence in receiving resistance genes; can transfer antibiotic resistance genes to other bacterial genera and species through mutations and/or receiving genetic elements via plasmids or transposons, Enterococcus spp. can cause severe problems in diagnosis, treatment, and control of the associated infections (3).…”
Section: Introductionmentioning
confidence: 99%